An Ultrastable and Easily Regenerated Hydrogen‐Bonded Organic Molecular Framework with Permanent Porosity. Issue 8 (16th January 2017) - Hu, Falu; Liu, Caiping; Wu, Mingyan; Pang, Jiandong; Jiang, Feilong; Yuan, Daqiang; Hong, Maochun
Abstract: A robust hydrogen‐bonded organic framework HOF‐TCBP (H4 TCBP=3, 3′, 5, 5′‐tetrakis‐(4‐carboxyphenyl)‐1, 1′‐biphenyl) has been successfully constructed and structurally characterized. It possesses a permanent 3D porous structure with a 5‐fold interpenetrateddia topological network. This activated HOF‐TCBP has a high BET surface area of 2066 m 2 g −1 and is capable of highly selective adsorption and separation of light hydrocarbons under ambient conditions. It shows excellent thermal stability, as demonstrated by PXRD experiments and N2 adsorption tests. Practical use of HOF‐TCBP is facilitated by the ease of its preparation and renewal through rotary evaporation. Abstract : A permanently porous molecular crystal, formed of hydrogen‐bonded 3, 3′, 5, 5′‐tetrakis‐(4‐carboxyphenyl)‐1, 1′‐biphenyl, was developed that possesses high BET surface area, excellent thermal stability, and easy regeneration. This combination of useful properties is rarely seen in other porous crystalline materials.